The transnational corporations in the Chilean economy - Eugenio Lahera P. (CEPAL Review, 1981)
The objective of this article is to analyse the presence and impact of the transnational corporations on the Chilean economy during the period 1974 1979. It is based to a large extent on a previous study made by the author which presents the empirical evidence and the methodology used in greater detail (Eugenio Lahera, Presencia y participación de las empresas transnacionales en la economía chilena, (E/CEPAL/B.235), August 1980). A substantial part of the statistical data, however, was especially updated for this article, which consist’ of three sections In the first section, the author briefly analyses the guiding principles behind government policy on foreign investments; in the second, he considers the variations undergone by direct foreign investment in Chile between 1974 and 1979; and in the third section he deals with the repercussions of rise transnational corporations on the economy of the country. This section is followed by the conclusions, among which the author lays particular stress on some which contrast with generally held views on this matter, rims, for example, although tire policies on foreign investments applied by the government during the period under consideration were very liberal, the average flow of direct foreign investment was smaller than that recorded in previous years and its accumulated total did not reach the levels of the late 1960s. Moreover, this investment has been concentrated in a few economic units, has been used primarily to purchase local enterprises or to strengthen existing foreign enterprises, and has been oriented towards the internal market. In short, it has not assumed an important role in the economic development of the country mill indeed, on die contrary, could the Ip to aggravate certain problems such as that of the external bottleneck.